Ombres et lumières sur les élections européennes des 7 et 10 juin 1979 : ébauche d’une première analyse des résultats - Seiler, Daniel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
This article seeks to provide a first attempt at finding a way through the intricate jungle created by at least nine political Systems electing members for one Parliament. The analysis is divided into four steps. The first step considers the actors and the rules of the game and results in a clear conclusion : neither the rules (the electoral Systems) nor the actors (European political parties) allow for the expression of any kind of political will. The second step of the analysis deals with some generalizations about the so-called European trends of the election. The "nonvoters' party" appears as the clear winner. Moreover, this is the only commonpattern observed in the nine countries.The third step is comprised of a country by country overview. Rather than referring to the European election, one should talk about at least elevent different elections each with a different set of issues. In terms of the issues, Denmark is the sole country where essentially European matters were in the forefront. In the other cases, the election of the MEP resembles an opinion poll designed especially to meet the needs of national leaders and parties. The article concludes by considering future developments. The real European elections will take place in 1984. What will happen from June 1979 until 1984 will be akin to rehersals for a play. The script seems well written and the dialogue is interesting. However, the actors (the parties) are untrained. The destiny of the performance will entirely depend on the actors.